Enzimatically modified penicilline biosensor/ Zainiharyati Mohd Zain, Marina Mokhtar and Wan Zarina Wan Kamaruddin. - Mohd Zain, Zainiharyati; Mokhtar, Marina; Wan Kamaruddin, Wan Zarina (2007)
A triiodide selective membrane electrode for the determination of penicillin in pharmaceutical formulation based on flow injection analysis (FIA) was developed. The principle of this system is based on classical iodometric penicillin assay, where the penicilloic acids resulted from enzymatic hydrolysis reaction were merged and reacted with triiodide solutions in the flow system. The excess triiodide was then detected by triiodide membrane detector. Under the adopted conditions, a sampling frequency of 75 samples per hour was obtained. The response was linear from 0.05 to 1.0 mmol L'1 (n = 4) and detection limit of 0.0025 mmol L"1. Good reproducibility (RSD±3.80 (n = 4)) was obtained for the determination of 0.5 mmol L'1 penicillin G. The enzymatic reactor is stable for more than 2 months while the triiodide membrane remained fuctional despite being continuously pumped for 25 hours. Good agreement was obtained between the proposed method and manufacturer’s claim values when applied to the analysis of pharmaceutical formulations.